METHODS EFFECTIVENESS IN PRACTICE DRIBBLE FOOTBALL GAME Model development exercise agility and reaction speed foot - Sudirman, S (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
Development research conducted has the primary objective is to produce a model practice agility and reaction speed of the foot in order to improve dribbling skills in the game of football Nikken UNM student. A development activities, can be done if there is a needs analysis based on data from field conditions. Based on these data will be compiled the development plan, and based on the plans drawn, then the development of the product to be applied. Approach to research and development is deemed appropriate for use in finding solutions to solving problems / issues in the field of education and training because its goal is not just to describe a fact or issue in training, but more than that of developed products and training are effective according to the conditions and real needs in the field. Products produced in research and development is a model practice agility and reaction speed foot aimed at enhancing the skills of dribbling in soccer game Nikken UNM student. Procedures or steps in the research are: 1) a preliminary study, which includes literature review and prasurvei, 2) develop a model, which includes limited trial, and the trial area, 3) validation of the model using experimental research design with Randomized Pretest -Posttest Control Group Design. Based on the information above it can be concluded as follows: There was a significant correlation agility training methods on the ability to dribble the soccer game proved the value r0 = -0.713 (P <0.05), There was a significant correlation method to the reaction speed drills dribbling ability in the game of football proved r0 = 0.685 (P <0.05), There was a significant relationship together between training methods agility and reaction speed training methods foot on the ability to dribble the soccer game proved r0 = 0.722 (P <0.05 ).